Rancang Bangun Menu Konfirmasi sebagai Pendukung Keputusan Klaim Jaminan Kesehatan Nasional Menggunakan Metode Extreme Programming - Najrifatussya'diah, Salsabila; Syahidin, Yuda; Yunengsih, Yuyun (Program Studi Teknik Informatika Universitas Pamulang, 2024)
With a focus and in-depth analysis of the case findings from research conducted at Hospital X, it was found that in the process of submitting claims for national health insurance incomplete patient data often hinders the claim submission process. Delays in claim submission can impact the hospital's finances and the quality of services. Therefore, the completeness of patient data is a crucial factor in the claim submission process. The purpose of this research is to design a confirmation menu to support decision-making for national health insurance claims using the extreme programming method. The main focus of this research is to develop a confirmation menu in the system to assist staff in addressing incomplete patient data. This design is built using the extreme programming method, which is considered more flexible, simple, and easy to adapt to frequently changing requests. As a result of this research, the application of the extreme programming method in system design can assist the staff involved in the claim process to confirm and communicate when patient data is incomplete. Additionally, this system can improve performance indexes and minimize hospital losses, thereby continuously enhancing excellent service delivery.